Central wage bargaining and local wage flexibility: evidence from the entire wage distribution - Thiess Büttner; Bernd Fitzenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
We argue that in labor markets with central wage bargaining wage flexibility varies systematically across the wage distribution: local wage flexibility is more relevant for the upper part of the wage distribution, and flexibility of wages negotiated under central wage bargaining affects the lower part of the wage distribution. Using a random sample of German socialsecurity accounts, we estimate wage flexibility across the wage distribution by means of quantile regressions. The results support our hypothesis, as employees with low wages have significantly lower local wage flexibility than high wage employees. This effect is particularly relevant for the lower educational groups. On the other hand, employees with low wages tend to have a higher wage flexibility with respect to national unemployment.
Keywords: 330; Central wage bargaining; Wage flexibility; Quantile regression; Lohnpolitik; Lohnstruktur; Regionale Lohnstruktur; Lohnrigidität; Schätzung; Deutschland